Optimization of alkali concentration in the pretreatment of sugarcane bagasse for ethanol production - Sujan, SM Asaduzzaman; Hossain, M; Uddin, M Nashir; Fakhruddin, ANM (Bangladesh Journal of Scientific and Industrial Research, 2023)
This study was aimed for the investigation of the effect of pretreatment procedure of alkaline, based on the chemical arrangement, surface morphology, structural composition and enzymatic assimilation of sugarcane bagasse for sugars and ethanol production. Alkali pretreatment (0 to 8% w/v of NaOH) assists to reduce the lignin portion (from 19.57±0.03% to 9.91±0.02%) and increase the cellulose content of the treated SB (from 34.66±0.05% to 63.58±0.05%) simultaneously. The optimal conditions for alkali pretreatment were 8% NaOH charge at 100oC for 90 min. Enzymatic digestibility of alkali treated SB was significantly improved and hydrolysis yield reached to 89.59% glucose and 61.23% xylose at an prime level using Trichoderma viridae. Further hydrolysate of 8% (w/v) alkali treated SB sample was fermented by Saccharomyces cerevisiae to convert sugar into ethanol and yield was 16.81±0.32% in 24 h. Alkali pretreatment was found to be a treatment of choice for cellulose hydrolysis in SB and subsequent sugar acquired for the production of ethanol during fermentation. Bangladesh J. Sci. Ind. Res. 58(2), 89-98, 2023